Analysis of Corporate Governance, Leverage and Company Size on the Integrity of Financial Statements - Aina Zahra Parinduri; Risma Koeshartanti Pratiwi; Oktavina Ika Purwaningtyas (Indonesian Management and Accounting Research, 2018)
The purpose of this study is to find empirical evidence of the effect of good corporate governance (Independent Board of Commissioners, Audit Committee, managerial ownership, institutional ownership), Leverage and Company Size on the integrity of financial statements. The sample used in the study was 33 companies listed in the LQ45 category on the Indonesia Stock Exchange (IDX) for the 2015-2017 period. This study uses the method of multiple linear regression analysis. The analytical tool used for hypothesis testing is SPSS 25. The results of this study indicate that the independent board of commissioners has a positive effect on the integrity of financial statements, institutional ownership has a positive effect on the integrity of financial statements. However, the audit committee, managerial ownership, leverage and company size have no influence on the integrity of financial statements.